Complement in Hemolysis- and Thrombosis- Related Diseases - Luo, Shanshan; Hu, Desheng; Wang, Moran; Zipfel, Peter F.; Hu, Yu (Frontiers in Immunology, 2020)
The complement system, originally classified as part of the innate immunity, is a tightly self-regulated system, consisting of liquid phase, cell surface and intracellular proteins. In the blood circulation, complement system, platelet, coagulation system and fibrinolysis system form a close and complex network. They activate and regulate each other, and jointly mediate immune monitoring and tissue homeostasis. The dysregulation of each cascade system results in clinical manifestations and the progression of different diseases, such as sepsis, systemic lupus erythematosus, or ischemia–reperfusion injury and so on. In this review, we summarize the crosstalk between the complement system, platelets, and coagulation, provide integrative insights into how complement dysfunction leads to hemopathic progression, and further discuss the therapeutic relevance of complement in hemolytic and thrombotic diseases.